Automatic Detection and Automatic Classification of Structures in Astronomical Images - Parada-Daza, V (SPIE, 2014)
The study of the astronomical structures is important to the astronomical community because it can help to identify objects, which can be classified based on their internal structure or their relation to other objects. For this reason, it is developed an automated tool to analyze astronomical images into its components. Firstly, a 2D images is decomposed into different spatial scales based on wavelet transform. Then, it is implemented a detection algorithms to each spatial scale, such as Clumpfind, Gaussclump, or Dendrogram techniques. The goal is to build a new algorithm and tool that is available to the community and satisfies the requirements of the next Chilean Virtual Observatory (ChiVO). © 2014 SPIE.